Aplikasi Absensi Berbasis Multiplatform Dengan Penerapan Location Based Service Dan Face Recognition Menggunakan Framework Flutter - Esa Surya Anggraini; Muhamad Alda (Universitas Budi Darma, 2025)
Manual attendance systems have many limitations, such as being susceptible to data manipulation, time consuming, and inefficient in managing attendance data. This study aims to build a Multiplatform-based attendance application implementing Location-Based Service (LBS) and Face Recognition technology by utilizing the Flutter framework. This application is designed to improve the accuracy, security, and efficiency of the attendance process at the Nur Adia Education Foundation. LBS technology is used to ensure that the user's location when taking attendance is in a predetermined area, while Face Recognition ensures that the user's face matches the facial data registered in the system. This study utilizes the Research and Development (R&D) method which begins with problem identification, needs analysis, system design, implementation, and application testing. The test results show that the application can validate the location and identity of the user quickly with a good level of accuracy. The Flutter framework enables cross-platform development with a user-friendly interface and optimal performance. This technology integration has successfully replaced the manual attendance method, providing a modern solution to support digital transformation in educational organizations. This research is expected to be the first step in adopting a technology-based system for more efficient and effective operational needs.